Aging, HIV and wellness: augmenting the components of successful aging. (June 2011) - Vance, David E; Bayless, Howard; Kempf, Mirjam-Collette; Keltner, Norman L; Fazeli, Pariya L
Pharmaceutical advances in suppressing viral replication of HIV has resulted in improved prognosis of those infected with HIV. As a result, adults infected with HIV are approaching nearly normal life expectancies. In fact by 2015, nearly half of those with HIV will be 50 years of age and older. Although the increase in life expectancy among HIV-positive patients heralds optimism in treating this disease in the long term, HIV remains incurable and may complicate one''s ability to age successfully. In this article, eight components necessary for successful aging (i.e., length of life, biological health, mental health, cognitive efficiency, social competence, productivity, personal control and life satisfaction) as posited by Baltes and Baltes will be delineated and described as they are compromised by HIV. Highlighted in this article will be prevention and intervention strategies to facilitate successful aging in this population. From this, implications for future research will be provided.